If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = (-5 + z) Remove parenthesis around (-5 + z) 16 = -5 + z Solving 16 = -5 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. 16 + -1z = -5 + z + -1z Combine like terms: z + -1z = 0 16 + -1z = -5 + 0 16 + -1z = -5 Add '-16' to each side of the equation. 16 + -16 + -1z = -5 + -16 Combine like terms: 16 + -16 = 0 0 + -1z = -5 + -16 -1z = -5 + -16 Combine like terms: -5 + -16 = -21 -1z = -21 Divide each side by '-1'. z = 21 Simplifying z = 21
| N/4-11=7 | | y=1+2x+2 | | (a+4)+2bi=6-5ib | | x+5=51 | | 26b=832 | | 15hc=-12 | | 4x-46=32-2x | | 2m+10+3m=180 | | y=-40x^2+1100x | | -y-7=-4 | | 3x^5-5x^3+15=0 | | 2*(x-3)=(x-1)+7 | | 4+16a= | | (a+4)+2bi=6-5i | | 3x+y=y+90 | | 8n-7(-6n-2)=-33+3n | | 22w=726 | | 2x^4+16x^2+32x=0 | | 3*(x+2)=-5-2*(x-3) | | 8y+-3x=20 | | 20-28x=132 | | 8y+-4y= | | 20y-17x=55 | | 2x-2(7x+12)=2(x+3) | | 8w+3-2w-8=6w-5 | | X+5+7x-2= | | 2x-2(7x+12)=2(x-3) | | 3.2p=52.5 | | y-14.6=-31.7 | | 3(4*-9)=23 | | 5-4x+10= | | 9=1/3p |